Masculinidades, Psicoterapia y Construccionismo Social - Cardoso, David Tiago (2022)
The aim of this article is to present Social Constructionism as a powerful psychotherapeutic approach for the care of (cis) men and their masculinities. To do this, we present relational social constructionist epistemologies and two dimensions that contribute to the changes sought by men. We highlight in the text how we recognize men and their masculinities through constructionist epistemologies and their dialogues with Feminist Gender Studies. It is through this epistemological inversion that therapeutic practice is constructed as a postmodern possibility that embraces the multiple narratives of the Self of men and their expressions of masculinity. To account for our narrative, we present the case of Rafael and how his therapeutic process led to the development of relational changes.